Methodology of word-centerism to children's language education in the works of French philosophers of the twentieth century (Pedagogy of Higher and Secondary Education, 2013)
Polevikova O. B. Methodology of word-centerism to children's language education in the works of French philosophers of the twentieth century.The author of the article examines the development of views on  language nature and function in the works of French philosophers of the twentieth century as the methodological basis of word-centerism approach to language education and speech development of preschool and primary school aged children.
Keywords: word-centerism; language education; French philosophers of the twentieth century